Journeys in Kerouac's On the Road - Pospíšilová, Jana (Univerzita Pardubice, 2016)
The aim of the bachelor paper is to provide an analysis of the significance of the "journey" in Jack Kerouac's On the Road. The theoretical part of the thesis outlines the definition of the journey and the ways this term can be understand from religious perspective in connection with the core book, especially how the inward spiritual journey evolved in tandem with the physical road trip. The chapter outlines the cultural and historical background of the Beat Generation and post-war society in the USA. All the mentioned ways are defined and elaborated in order to be clear with the usage of relevant literature sources connected to the Beat Generation and literature, American literature in general and mid-20th century fiction. The analytical part includes the application of the information explained in the theoretical part into practice, explores the importance of the physical journey as well as the one into person's inside and their interconnection and discusses the aspects of a journey. The idea of mobility and whether the journey in the On the Road is just the way of running away from society or whether it portrays the form of a protest and finding is also focused on.
Cesty v románu Na cestě od Jacka Kerouaca
Keywords: Kerouac, Jack; inner journey; Beat Generation; consumer society; Buddhism; Kerouac, Jack; vnitřní cesta; Beatnická generace; konzumní společnost; Buddhismus